A Rare Case of Monocular Visual Loss after Spinal Surgery in Prone Position with Adequate Eye Protection - Babu, Naresh Kannan; Kohli, Piyush; Palaniappan, Suresh; Krishnamurthi, Ilango; Ramasamy, Kim (Indian Journal of Neurosurgery, 2019)
The aim of this case report is to present a rare case of monocular visual loss after spinal surgery in prone position with adequate eye protection. A 38-year-old healthy woman underwent an uncomplicated cervical surgery in prone position, while her head was supported on a foam cushion horseshoe headrest. Immediately after recovery, the patient complained of loss of vision in her left eye. Her best-corrected visual acuity was perception of light. Ocular examination was suggestive of central retinal artery occlusion (CRAO). Blood investigations, carotid Doppler, echography, and computed tomography scan were normal. The incidence of CRAO has decreased in the past decade due to the use of appropriate head rest. In addition to following the guidelines laid by the Perioperative Visual Loss (POVL) Task Force of American Society of Anesthesiologists, attention must be paid to avoid any accidental intraoperative movement of the patient. Checking the eyes intermittently is not a foolproof method for preventing compression. New headrests need to be designed, which will allow continuous monitoring of the patient lying in prone position.
Keywords: central retinal artery occlusion; perioperative visual loss; prone; spinal; headrest